(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The concern of the world community with the growth of terrorist activity is due to the large number of victims of terrorists and the huge material damage caused by terror, as well as the fact that, thanks to the development of the latest dual-use technologies, the activities of the media and global computer networks (Internet), extreme commercialization in the field of so-called. n. masses of culture where violence and cruelty are cultivated, an increasing number of people have the opportunity to receive and then use information about the creation of the most sophisticated means of destruction and how to use them. Neither highly developed countries nor countries lagging behind in economic and social development with different political regimes and state structures are immune from outbreaks of terrorism.